2005
DOI: 10.1021/jm049762l
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Activity Relationships of Pregabalin and Analogues That Target the α2-δ Protein

Abstract: Pregabalin exhibits robust activity in preclinical assays indicative of potential antiepileptic, anxiolytic, and antihyperalgesic clinical efficacy. It binds with high affinity to the alpha(2)-delta subunit of voltage-gated calcium channels and is a substrate of the system L neutral amino acid transporter. A series of pregabalin analogues were prepared and evaluated for their alpha(2)-delta binding affinity as demonstrated by their ability to inhibit binding of [(3)H]gabapentin to pig brain membranes and for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
104
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(114 citation statements)
references
References 52 publications
9
104
0
1
Order By: Relevance
“…96,97 Recently, it has become apparent that the molecular targets for gabapentin and pregabalin are ␣2-␦ proteins, specifically ␣2-␦-1 and ␣2-␦-2. 98,99 The evidence supporting this concept has been reviewed. 55 At present, the exact way in which binding to these proteins protects against seizures is not fully understood.…”
Section: Voltage-gated Calcium Channelsmentioning
confidence: 99%
“…96,97 Recently, it has become apparent that the molecular targets for gabapentin and pregabalin are ␣2-␦ proteins, specifically ␣2-␦-1 and ␣2-␦-2. 98,99 The evidence supporting this concept has been reviewed. 55 At present, the exact way in which binding to these proteins protects against seizures is not fully understood.…”
Section: Voltage-gated Calcium Channelsmentioning
confidence: 99%
“…Interestingly, the structure-activity relationships for α2δ and system L transporter activity are distinct. Optimizing α2δ modulatory activity to produce an intrinsically superior anticonvulsant substance would not necessarily result in a clinically useful AED since system L transporter substrate activity must be retained (Belliotti et al, 2005). In contrast to in vitro screening approaches, animal test systems only select compounds that are inherently anticonvulsant and are able to access the relevant brain targets.…”
Section: Is Screening In Animal Models Necessary?mentioning
confidence: 99%
“…2). The structural requirements for α 2 -δ binding differ from those that confer system L substrate activity (Belliotti et al, 2005). Both S(+)-and R(−)-isobutyl GABA are system L substrates (IC 50 values for inhibition of [ 3 H]L-leucine uptake are 158 and 355 μM, respectively), but the S-enantiomer (pregabalin) binds to α 2 -δ with 10-fold greater affinity than the R-enantiomer.…”
mentioning
confidence: 98%
“…Mutagenesis experiments have shown that the anticonvulsant binding site is probably confined to the α 2 protein and/or the external portion of the associated δ component (Brown and Gee, 1998;Wang et al, 1999). Recent structure-activity studies with a variety of compounds related to gabapentin and pregabalin suggest that high affinity binding to α 2 -δ is required for anticonvulsant activity with compounds structurally similar to these drugs (Bryans et al, 1998;Belliotti et al, 2005).…”
mentioning
confidence: 99%